ANALYSIS OF LITHUANIAN POLITICAL SCIENCE FIELD: EXPLAINING DIFFERENT PERCEPTIONS OF POLITICAL SCIENCE - Strakšaitė, Justė (Politologija, 2015)
On purpose to analyse a certain part of social world it is useful to apply a concept of field introduced in the field theory of French sociologist Pierre Bourdieu. Field is a structure of relations between the objective positions occupied by its agents. The positions of the agents, their success, recognition and distinction in the field depend on special resources they own, called capital. According to Bourdieu, capital determines the habitus of the field agents. Habitus might be understood as a set of dispositions, perceptions and beliefs inherent to an individual. It is the result of the internalization of external economic, social, cultural conditions and practices, contrary to popular belief that it depends only on subjective individual experience.Two types of cultural capital – academic and scientific capital – are authentic to scientific field. Although the activity of the agents of scientific field might look disinterested and based only on intellectual principles, in reality this field is a subject to competition for better positions like all other fields. Beyond the normative and philosophical disputes on perceptions of science may be hidden interests to impose such principles which could bring the highest benefit to the field agents.Normative discussions about the perceptions of science are common in a field of political science as well. Mostly they are related to the question of the purpose of political science (whether it should be “pure” science or to focus on real political problems), methodological orientations (positivist vs. anti-positivist approach), attitude towards internationality of political science (local or cosmopolitan) and its relation to other disciplines (autonomy of political science). In the article these perceptions of political science are considered as dispositions of political scientists composing a part of their habitus. Since habitus is structured by capital, a research hypothesis that the perceptions are related to certain types of capital was proposed.Lithuanian political science field was chosen as the object of the research. The main problem analysed in the article is the “origin” of different perceptions of political science If only individual experience affects these perceptions, how could we explain the fact that some beliefs are more typical to certain groups of scientists and are not inherent to other groups?The investigation using semi-structuralized survey method was executed. Eighty-eight Lithuanian political scientists took part in the research. Received data was analysed by multiple correspondence analysis technique and other methods of statistical analysis. It was identified that those political scientists who own the highest academic and scientific capital tend to support a vision of political science not oriented towards practical politics. They also give priority to the national, local political science and to the positivist approach. Sociology and partly philosophy disciplines are privileged among them. On the other hand, those scientists who have higher economic and political capital (extraneous capital to scientific field) are more liable to support practical and cosmopolitan orientations, disciplines of economics, administration and management. Also a relation between the education of political scientists and their perceptions was established.These results might be interpreted as demonstrating the above mentioned interests to impose such perceptions of political science which could be the most useful to the scientists and as confirming the hypothesis of the research.